World Gold Price Prediction After United State Election Using Pulse Function Intervention Analysis - Sediono Sediono; Anggi Triya Vionita; Fayza Shafira Renianti (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2025)
The United States (US) election in November 2024 had a significant impact on global economic conditions, especially world gold prices. A key effect was the strengthening of the US dollar, leading to a sharp drop in gold prices to 2,582.1 USD. This study aims to model and forecast gold prices using the pulse function intervention analysis method. The analysis uses weekly data, with the intervention point set in the second week of November 2024 (t = 101). The best pre-intervention model was identified as ARIMA(0,2,1), while the best intervention model had orders b = 1, r = 0, s = 0, based on analysis of the Cross Correlation Function (CCF). The resulting model shows significant parameters and strong performance, with a MAPE of 1.51%, AIC of -530.394, SBC of -525.030, and MSE of 0.0002037. Forecasts indicate gold prices are likely to increase again through the end of July 2025. These findings show that the pulse intervention model effectively captures external shocks, such as post-election dollar appreciation. The study improves our understanding of the dynamics of global gold prices and offers insights that can help policymakers develop strategies to mitigate the risks caused by fluctuations in the external market.